2015
DOI: 10.1111/nyas.12816
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer nanotechnology for enhanced formulation and controlled delivery of resveratrol

Abstract: In spite of its wide and beneficial pharmacological potential, resveratrol lags behind other compounds because of its comparatively less impressive pharmacokinetic profile. Resveratrol has very low oral bioavailability and, from a formulation perspective, it has low solubility in water, which leads to its poor absorption upon oral administration. Apart from low aqueous solubility, resveratrol has poor metabolic stability and instability at high pH, and is photosensitive. The pharmacokinetic and formulation-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Dendrimers have been successfully shown to improve transdermal drug delivery, but most of the reports available are on PAMAM dendrimers (Chauhan et al, 2003, Cheng, 2007Chauhan, 2015). Some of the widely used dendrimers including PAMAM dendrimers have been reported to be toxic in many studies (Jevprasesphant et The reports on the use of peptide dendrimers for transdermal delivery are limited to our research group.…”
Section: Introductionmentioning
confidence: 77%
“…Dendrimers have been successfully shown to improve transdermal drug delivery, but most of the reports available are on PAMAM dendrimers (Chauhan et al, 2003, Cheng, 2007Chauhan, 2015). Some of the widely used dendrimers including PAMAM dendrimers have been reported to be toxic in many studies (Jevprasesphant et The reports on the use of peptide dendrimers for transdermal delivery are limited to our research group.…”
Section: Introductionmentioning
confidence: 77%
“…In our previous studies, different chain lengths of bromoalkylcarboxylates were conjugated with different percentage of primary amines of PAMAMs and PPIs. The results showed that 30% substitution of primary amines by 10-bromodecanoic group resulted in higher gene transfection efficiency and lower cytotoxicity compared to other formulations (Ayatollahi et al 2015, Hashemi et al 2013, 2015). In the current study, we modified the surface layer of PAMAM G4 and PPI G4 by 30% surface primary amines grafting with 10-bromodecanoic acid and explored their potential as solubility enhancers and drug delivery carriers.…”
Section: Discussionmentioning
confidence: 95%
“…Such modifications may alter the host-guest interactions, and thereby increase the solubility. In our previous studies, it was shown that alkylation of PAMAM and PPI could reduce their cytotoxicity and enhance gene delivery efficiency (Ayatollahi et al 2015, Hashemi et al 2013, 2015. Accordingly, the aim of this study was to evaluate the performance of alkyl-modified PPI G4 and PAMAM G4 derivatives as enhancers of solubility and antitumor activity of crocetin.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regardless of the extensive research, the information on the drug plasma level still stays dim [59]. A few activities have been going onto overcome the limitation of resveratrol using several methods such as nanoparticle technology, niosomes, and nanovesicles [60][61][62][63][64][65][66]. Researcher utilized NSs to enhance the solvency, soundness, and skin penetrability of resveratrol [67].…”
Section: Curcuminmentioning
confidence: 99%